Aglomerasi dan Pengaruh Aliran Dana Sektor Moneter pada Pertumbuhan Sektor Riil di Wilayah Cilacap – Banyumas dan Sekitarnya - Kamio Kamio; Abdul Aziz Ahmad (EKO-REGIONAL, 2011)
The  determining Cilacap District as an economic core area of southwest Central Java should be assisted in such a way soas to be able to significantly accelerate the growth of the regions and  whole of the south area. Based on the region potential mapping, this research found that the real sector activities in Cilacap was more dominance than the other district in south area. So were the financial activities, flow of loan to manufacturing sector in Cilacap also dominance comparred to the other regions. From human development side, Cilacap, as indicated by rising Human Development Index and higher rate of income per capita of most of the inhabitant, had a better condition than other region. The main obstacle to develop industrial area in the region  was lack and low quality of infrastructure. Inexpediently condition of road and lack of effort to improve the infrastructure would impede new investment. According to parameter of causality relationshp between real and financial sector of the region, advancement of real sector was supported by productive financially sector. High loan to deposit ratio in the region will encourage regional development and economic growth, especially as long as non-consumptive loan had been improved, it  would push  the manufacturing industris growth up. Keywords:        economic core area, region potential mapping, infrastructure, human quality, own source revenue